Intra-articular Steroids vs Saline for Lumbar Z-Joint Pain: A Prospective, Randomized, Double-Blind Placebo-Controlled Trial. Issue 2 (12th December 2018) - Kennedy, David J; Fraiser, Ryan; Zheng, Patricia; Huynh, Lisa; Levin, Joshua; Smuck, Matthew; Schneider, Byron J
Abstract: Objective: To determine if intra-articular (IA) injection of corticosteroids is effective in reducing the need for radiofrequency ablation (RFA) in those with dual comparative medial branch block (MBB)–confirmed lumbar z-joint pain. Design: This was a randomized, double blind, placebo-controlled study. Setting: Two academic medical centers. Subjects: Fifty-six consecutive subjects who had ≥80% pain relief during an initial screening MBB were recruited. Methods: Patients received a second confirmatory MBB and concurrent IA injection of either corticosteroid or saline per randomization. Twenty-nine of 56 received intra-articular corticosteroid (triamcinolone 20 mg), of whom 24 also had a positive confirmatory MBB per Spine Interventional Society guidelines, with ≥80% pain relief from both MBBs. Twenty-seven of 56 received IA saline into the z-joint during the confirmatory MBB, of whom 22 also had a positive confirmatory MBB. The primary outcome measure was the categorical need for RFA due to insufficient pain relief with intra-articular injection, and the secondary outcome was time to RFA. Results: There was no statistically significant difference in the need for an RFA between the groups (16/24 steroid, 67%, 95% confidence interval [CI] = 47–82%) vs 15/22 saline (68%, 95% CI = 47–84%, P  = 1.00). The average time to RFA was also not different, at 6.00 weeks for steroids vs 6.55 weeks for saline ( P  = 0.82). Conclusions: Intra-articular corticosteroids were not effective in reducing the need for or the time to a radiofrequency ablation of the medial branches in those with dual MBB–confirmed lumbar z-joint pain.